IMPACT MECHANISMS RESEARCH IN THE CONTACT NETWORK ON RAIL TRACK CIRCUITS - Shcheka, V. I. (Science and Transport Progress, 2015)
Purpose. Еlectromagnetic processes in «contact network-rails-earth»system should be researched for the purpose of electromagnetic compatibility rail circuits with traction power supply system providing and improving traffic safety on railway transport. Methodology. The methods of scientific analysis, mathematical modeling, experimental investigation, scale modeling have been applied to achieve this goal. Findings. Conducted theoretical and experimental investigations, indicate that electromagnetic processes in the «contact network-rails-earth» system in nearest zone in frequency range up to 1 MHz and it give us an opportunity to consider, that electromagnetic field of hindrance consists of two components: electric and magnetic. Each of them has its own mechanism to influence the rail circuits. In consequence of research the theoretical and experimental dependences of electromotive force induced in wire-receiver from the hindrance current frequency have been received. The frequency graph of relative error according to data «theory-experiment» has been received. The adequacy by Wilcoxon criterion of mathematical model to experimental data has been proved. Originality. The results of theoretical and experimental investigations of magnetic influence between two contours gives us a concurrence in frequency range up to 1000 Hz with average relative error 2, 33 %. With hindrance current frequency one can observe certain increasing the average relative error between calculated and measured values of electromotive force induced in the wire-receiver. Practical value. The adequacy by Wilcoxon criterion of mathematical model to experimental data has been proved on significance level 5 %. It gives an opportunity to use this mathematical apparatus for the investigation of electromagnetic processes in lines with plenty of wires and in «contact network-rails-earth»system in range up to 1000 Hz. The obtained results can be useful in designing, researching and providing electromagnetic compatibility of rail circuits with traction power supply system.